A Study of Socio-economic Profile of Sorghum growers in U.P Bundelkhand region - Pragya; Mani Prakash Shukla (Epistemik Press, 2026)
Sorghum (Sorghum bicolor L.), often referred to as the “King of Millets,” serves as a crucial dryland crop supporting rural livelihoods in arid and semi-arid regions. Although the overall cultivation area in India has declined in recent years, increasing productivity trends highlight the importance of examining the socio-economic characteristics of its farmers. This study investigates the socio-economic profile of sorghum growers in the Banda District during 2022. A multistage sampling approach was employed to select 120 respondents from the Baberu and Naraini blocks. The analysis, based on descriptive statistics, indicates that marginal farmers represent the largest proportion (43.33%), while medium-scale farmers account for the majority of cultivated land (46.52%), with an average landholding size of 5.14 hectares. Educational levels among respondents are largely concentrated at the primary and secondary stages, with an illiteracy rate of 16.66%. In terms of living conditions, 70.83% of respondents reside in permanent (pucca) housing, and agriculture remains the main source of livelihood for 58.33% of the sample population. These findings emphasize the dominance of smallholder and marginal farmers, highlighting the need for targeted interventions, particularly in capacity building and training programs, to improve productivity and enhance the socio-economic well-being of farming communities. Keywords: Dryland agriculture, marginal farmers, landholding structure, occupational pattern, productivity trends.